IMPLEMENTASI SISTEM INFORMASI AKUNTANSI PERSEDIAAN PADA UKM BATIK DI KLATEN: SEBUAH STUDI KASUS - Hatta, Atika Jauharia; Muadzi, Galuh Rama; Indraswono, Cahyo; Marwanta, Y. Yohakim (AKUNTANSI DEWANTARA, 2025)
This study aims to analyze the condition of the inventory accounting system, making design and implement the Batik Tulis Kunayah accounting information system in Klaten Regency. The subjects of this research were the SME Batik Tulis Kunayah actors in Klaten Regency, with the research procedures used being observation, interviews, documentation and training. This study used data presentation methods, development models, and drawing conclusions for the data analysis techniques. The results of the study in the form of designing an inventory accounting information system will then be implemented by SME Batik Tulis Kunayah in its business as an effort to apply the digital marketing concept. The implementation of an inventory accounting information system in Batik Tulis Kunayah SME has enormous potential to increase efficiency, data accuracy and the quality of decision making. implementation of an inventory accounting information system for UKM Batik Tulis Kunayah have enormous potential to improve efficiency, data accuracy and the quality of decision making. By this information, various benefits such as process automation, error reduction, increased productivity, and data acquisition can be achieved regularly.